A SCOPING REVIEW OF MHEALTH TECHNOLOGIES FOR PATIENTS UNDERGOING HAEMODIALYSIS - Amalia, Sarah; Rochmawati, Erna (Indonesian Journal of Health Administration (Jurnal Administrasi Kesehatan Indonesia), 2024)
Background: The prevalence of patients requiring haemodialysis increases annually, highlighting the need for improved quality of care. Haemodialysis care involves several key aspects, including monitoring, education, and patient connectivity. The availability of mobile health (mHealth) technology enhances the effectiveness and efficiency of patient monitoring compared to conventional methods, ultimately improving patients’ quality of life. Aims: To map the development, types, and impact of mHealth technologies on patients undergoing haemodialysis. Methods: We conducted a scoping review following the Arksey and O’Malley methodological framework. We searched PubMed, Scopus, ScienceDirect, Google Scholar, CINAHL, and Sage Journals to identify relevant studies describing integrated mobile health applications for monitoring patients with CKD undergoing haemodialysis. Two independent reviewers screened and categorised findings based on predefined synthesis questions. Eleven studies representing various mHealth technologies were included. The PRISMA-ScR guidelines for scoping reviews were followed to ensure comprehensive reporting of results. Results: Out of 1,200 papers, 11 studies representing mHealth technologies were included. Most respondents were patients, though several articles also involved healthcare providers. We map our findings into three themes: the functionality of the applications, the types and features of mHealth technologies, and their impact. Conclusion: mHealth can be implemented as web-based or application-based platforms, offering innovative solutions for monitoring, education, and enhanced connectivity between patients and healthcare providers. Keywords: mHealth, haemodialysis, quality of life, monitoring, CKD